Pratiche di cittadinanza. L’associazionismo migrante femminile nel napoletano - Gatti, Rosa (SocietàMutamentoPolitica, 2016)
The paper re-articulates the relation between immigration and citizenship in a gender perspective. The analysis of citizenship practices exercised by migrant women in the local context allows to make visible their mobilization and participation to the public sphere. The analysis, based on interviews with the presidents of the migrants associations in Campania, explores the reasons whereby migrants women undertake participatory activities within their associations, the ways in which they move from informal networks to formal associations and take leadership, as well as barriers and factors that can help to overcome them. The actions of migrant women engaged in the voluntary sector show their capacity to intervene politically and socially, even when they are not recognized as citizens, challenging our idea of citizenship and showing the growing importance of the practices of citizenship.